2021
DOI: 10.1007/s10640-021-00603-8
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19’s U.S. Temperature Response Profile

Abstract: We estimate the U.S. temperature response profile (TRP) for COVID-19 and show it is highly sensitive to temperature variation. Replacing the erratic daily death counts U.S. states initially reported with counts based on death certificate date, we build a week-ahead statistical forecasting model that explains most of their daily variation (R2 = 0.97) and isolates COVID-19’s TRP (p < 0.001). These counts, normalized at 31 °C (U.S. mid-summer average), scale up to 160% at 5 °C in the static case where the infe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Carson et al. ( 2021 ) showed that Alpha variant was substantially more temperature sensitive, with humidity insignificant in the fitted models. According to Duong ( 2021 ) and Zhao et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carson et al. ( 2021 ) showed that Alpha variant was substantially more temperature sensitive, with humidity insignificant in the fitted models. According to Duong ( 2021 ) and Zhao et al.…”
Section: Discussionmentioning
confidence: 99%
“…On the whole, Delta spread much faster from the central region to the southeast, while Alpha spread from the north and south to the middle. Carson et al (2021) showed that Alpha variant was substantially more temperature sensitive, with humidity insignificant in the fitted models. According to Duong (2021) and Zhao et al (2022), Alpha is 50% more transmissible than the original strain, and thus frequent community mobility and dense population will definitely accelerate the spread of the virus.…”
Section: Covid-19 Delta Cases Estimationmentioning
confidence: 96%
“…To the best of our knowledge, most studies have examined the relationship between climatic factors, especially temperature, and the incidence, not mortality of COVID-19 in the United States, with time span usually less than six months [ [16] , [17] , [18] ]. Carson R.T. et al [ 19 ] concluded that COVID-19 death counts are strongly influenced by changes in maximum daily temperature. However, Karimi S.M [ 20 ] collected weather data of 3141 US counties, including minimum and maximum daily temperature, precipitation, ozone concentration, PM2.5 concentrations, and U.V.…”
Section: Introductionmentioning
confidence: 99%